2020
DOI: 10.1111/jir.12740
|View full text |Cite
|
Sign up to set email alerts
|

Supporting individuals with intellectual and developmental disability during the first 100 days of the COVID‐19 outbreak in the USA

Abstract: Background It is unknown how the novel Coronavirus SARS‐CoV‐2, the cause of the current acute respiratory illness COVID‐19 pandemic that has infected millions of people, affects people with intellectual and developmental disability (IDD). The aim of this study is to describe how individuals with IDD have been affected in the first 100 days of the COVID‐19 pandemic. Methods Shortly after the first COVID‐19 case was reported in the USA, our organisation, which provides continuous support for over 11 000 individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 4 publications
1
35
0
1
Order By: Relevance
“…Of note, we did not find any indication that living in residential care facilities or the level of intellectual disability increases the risk for COVID-19 related hospitalization or mortality. It has been reported that individuals living in residential care facilities are more vulnerable to COVID-19 infection [32] , but it has also been noted by other authors “that people with [intellectual and developmental disabilities] living in congregate care settings can benefit from a coordinated approach to infection control, case identification and cohorting” [33] . Possibly as evidence of adequate management or rapid response in many of these facilities, we observed in our study population that infected individuals in congregate care settings were not more vulnerable to adverse outcomes of disease than those living with their families.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, we did not find any indication that living in residential care facilities or the level of intellectual disability increases the risk for COVID-19 related hospitalization or mortality. It has been reported that individuals living in residential care facilities are more vulnerable to COVID-19 infection [32] , but it has also been noted by other authors “that people with [intellectual and developmental disabilities] living in congregate care settings can benefit from a coordinated approach to infection control, case identification and cohorting” [33] . Possibly as evidence of adequate management or rapid response in many of these facilities, we observed in our study population that infected individuals in congregate care settings were not more vulnerable to adverse outcomes of disease than those living with their families.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, we did not find any indication that living in residential care facilities or the level of intellectual disability increases the risk for COVID-19 related hospitalization or mortality. It has been reported that individuals living in residential care facilities are more vulnerable to COVID-19 infection 29 , but it has also been noted by other authors "that people with [intellectual and developmental disabilities] living in congregate care settings can benefit from a coordinated approach to infection control, case identification and cohorting" 30 . Possibly as evidence of adequate management or rapid response in many of these facilities, we observed in our study population that infected individuals in congregate care settings were not more vulnerable to adverse outcomes of disease than those living with their families.…”
Section: Discussionmentioning
confidence: 99%
“…19 Mills et al report that 1.3% of all homes for people with intellectual and developmental disability in the US supported by their organisation (including community-based sites, such as family and foster care homes, as well as institutional homes) had at least one person with confirmed COVID-19 over a 100-day period, although testing was limited to symptomatic individuals. 46 The Office for National Statistics (ONS) for England conducted a large survey and found that 56% of all care homes catering to people living with dementia and older people had at least one person who contracted confirmed COVID-19. 62 Higher levels of infection among residents were associated with prevalence of infection among staff, the use of bank or agency nurses, and different regions.…”
Section: Evidence On Burden Of Disease In the Long-term Care Sectormentioning
confidence: 99%